HOCl‐Activated Aggregation of Gold Nanoparticles for Multimodality Therapy of Tumors. Issue 17 (8th July 2021) - Liu, Dongya; Liu, Lingyan; Liu, Feiyang; Zhang, Mengfan; Wei, Peng; Yi, Tao
Abstract: Tumor microenvironment‐responsive nanodrugs offer promising opportunities for imaging‐guided precision therapy with reduced side effects. Considering that the antitumor effect is closely related to the size of the nanodrugs, it is particularly important to develop a therapeutic system with size adjustability in the tumor microenvironment, which is still a great challenge in the field of nanotheranostics. Herein, a reactive oxygen species (ROS)‐activated aggregation strategy is reported for imaging‐guided precision therapy of tumors. The ROS‐activated nanoplatform is constructed based on gold nanoparticles (AuNPs) coated with an HOCl probe on its surface (namely, Au–MB–PEG NPs). The Au–MB–PEG NPs show high sensitivity toward HOCl, resulting in the modulation of surface charge and rapid aggregation of AuNPs, and simultaneous release of methylene blue as a photosensitizer for photodynamic therapy (PDT). In the tumor environment, the aggregated AuNPs ensure higher tumor accumulation and retention. Furthermore, the redshift of the absorption of aggregated AuNPs leads to activated photoacoustic imaging signals and photothermal therapy (PTT) under near‐infrared irradiation. Au–MB–PEG NPs thus efficiently inhibit the tumor growth through combined PTT–PDT therapy. This work contributes to the design of stimuli‐induced size‐aggregation nanodrugs, thereby attaining advanced performance in cancer diagnosis and treatment. Abstract : A reactive oxygen species (ROS)‐activated aggregation strategy is constructed based on gold nanoparticles (AuNPs) coated with an HOCl probe. The as‐prepared nanoreagent shows high sensitivity toward HOCl, resulting in rapid aggregation of AuNPs for activated photoacoustic imaging and photothermal therapy, and simultaneous release of methylene blue as a photosensitizer for photodynamic therapy. The HOCl‐activated theranostic platform thus attains advanced performance in cancer treatment.